Trends in Small Business Management and Entrepreneurship Education in the United States - Solomon, George T.; Fernald, Lloyd W. (Entrepreneurship Theory and Practice, 1991)
The critical importance of small business management and entrepreneurship in determining the future of the economic and social well-being of the United States is generally accepted by leading experts in government and business. While there clearly is a boom in entrepreneurial enterprise throughout the nation, the extent of the growth in the educational services supporting this effort is at best only partially known through prior studies, such as those of Vesper (1985). This paper reports the results of three surveys on the development of courses, academic programs, seminars, and workshops in small business management and entrepreneurship in the U.S. The survey results point to a dramatic change in the number of colleges and universities that are now offering small business management and entrepreneurship courses and programs and in the quantity and scope of the courses offered within schools.